Unequal Bequests - Marco Francesconi; Robert Pollak; Domenico Tabasso (Institute for the Study of Labor (IZA), 2015)
Using data from the Health and Retirement Study (HRS), we make two contributions to the literature on end-of-life transfers. First, we show that unequal bequests are much more common than generally recognized, with one-third of parents with wills planning to divide their estates unequally among their children. These plans for unequal division are particularly concentrated in complex families, that is, families with stepchildren and families with genetic children with whom the parent has had no contact (e.g., children from previous marriages). We find that in complex families past and current contact between parents and children reduces or eliminates unequal bequests. Second, although the literature focuses on the bequest intentions of parents who have made wills, we find that many elderly Americans have not made wills. Although the probability of having a will increases with age, 30 percent of HRS respondents aged 70 and over have no wills. Of HRS respondents who died between 1995 and 2010, 38 percent died intestate (i.e., without wills). Thus, focusing exclusively on the bequest intentions of parents who have made wills provides an incomplete and misleading picture of end-of-life transfers.
Keywords: D13; J12; K36; 330; bequests; intergenerational transfers; altruism; exchange; evolutionary motives; family structure